Study of the unit trust industry in Singapore - Chong, Jessie Fere Lian (2015)
Unit trust is a relatively new form of investment medium in Singapore. This could account for its size which is many times smaller than that of Hong Kong, which is considered Singapore's closest competitor as a financial centre in Asia. There are three types of unit trust funds in Singapore, There are namely, Growth, Income and Balanced Funds. a total of 27 unit trust funds managed by only 7 companies. Unit trust in Singapore can also be classified into trusts which are approved and trust which are unapproved. Approved unit trusts face a less complicated tax system, which some fund managers in the interviews find it less progressive. The government however is eager to promote unit trust's status as an investment medium for both fund managers and investors by tippling a fine balance between excessive regulation and lack of regulation. In this project, many problems were highlighted and many solutions were recommended. However, that the ultimate solutions are : to form a unit trust association, an independent body to govern the operations and regulation of the unit trust and to educate the public at large. Perhaps, the government should step in to help in these areas for it would help to improve the economy. Lastly, the unit trust industry in Singapore is still young and its rapid growth in the recent years show promise of its importance in Singapore in the future.